No benefit of soluble fiber on liver function - Ghavami, Abed; Talebi, Sepide; Barghchi, Hanieh; Nattagh-Eshtivani, Elyas; Mohammadi, Hamed; Ziaei, Rahele (International journal for vitamin and nutrition research, 2024)
To conduct a systematic review and dose-response meta-analysis of current findings from randomized controlled trials (RCTs) on the effect of soluble fiber supplementation on liver function in both healthy individuals and people with specific health conditions, PubMed, Scopus, and ISI Web of Science were systematically searched for relevant RCTs published prior to April 2022. We estimated the change in liver function parameters for each 5 g/d increment in soluble fiber in each trial and then calculated the mean difference (MD) and 95%CI. A total of 25 RCTs with 27 treatment arms (1744 subjects; 884 cases, 860 controls) were included. A total of 25 RCTs with 27 treatment arms were included. The intervention duration of the included studies ranged from 3 to 52 weeks and the dose of soluble fiber supplementation varied from 0.0025 to 40 g/d. Soluble fiber supplementation could not significantly affect serum alanine transaminase (MD: -0.02 U/L, 95% CI: -1.06 to 1.01), aspartate transaminase (MD: -0.34 U/L, 95% CI: -0.84 to 0.15), alkaline phosphatase (MD: 0.29 U/L, -0.14 to 0.71), gamma-glutamyl transferase (MD: 0.12 U/L; 95% CI: -0.81 to 1.05), serum bilirubin (MD: 0.42μmol/L, 95% CI: -0.08 to 0.93) and albumin (MD: 0.64 g/dl, 95% CI: -0.42 to 1.70) levels. Findings from this study did not support the beneficial effects of soluble fiber supplementation on liver function biomarkers. There is a need for long-term high-quality interventions to examine the effects of different types and doses of soluble fibers on liver function as primary outcome.